Psychological factors of the effectiveness of competitive activity in professional skills - A. Yu. Tymchikov (Вестник университета, 2022)
The results of psychological studies of the factors of the effectiveness of competitive activity in professional skills are presented. The psychological content of this activity, its connection with competitive activity is revealed. The main method of empirical research of psychological factors of the effectiveness of competitive activity in professional skills was a comparative analysis of highly and poorly effective activities, as well as personal and professional qualities of their subjects. For this purpose, the survey of winners and prize-winners of professional skills competitions, as well as those participants who performed unsuccessfully, was used. The main psychological determinants that ensure successful performance at professional skill competitions with a high level of instrumental readiness are identified. The main psychological reasons for unsuccessful performances are identified - excessive independence with insufficient experience of psychological training; insufficient command of psychological technologies of self-action; low need for achievements, blurred fuzzy image of “I am the winner”; inadequate (overestimated and understated) self-esteem; unproductive reflection, low level of reflective culture; insufficient level of development of the main personal and professional qualities; uncertainty.